Human Rights Violation Kashmir: A Study on Indo-Pak Relations: Exploring the impact of human rights violations on the Kashmir conflict (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The Kashmir conflict is one of the most longstanding and intractable issue between India and Pakistan. The dynamic nature of the conflict affects the lives of millions of people, across political, social, economic and cultural spheres. Kashmir is primarily a dispute about justice and people, although its territorial dimensions are complicated enough. The dispute has become firmly wedged in the internal politics of both countries. Kashmir found in the minds of politicians, strategists and scholars a place where national and sub national identities are ranged against each other. The study analyses the importance of human rights violations in Kashmir. The conflict in this Kashmir is as much as clash between identities, imagination and history as it is a conflict over territory, resources and people. The emergence of human rights violations increased after the eruption of insurgency in 1989 and these aspects were also examined in the paper. The incidents of human rights violation were also discussed in the study. The study is significant as far it touched how far the incidents of human rights violation affected the people in Jammu Kashmir over these years